The Effect of Learning Leadership and Work Motivation on the Performance Teachers of SMP Negeri in Kecamatan Baguala, Ambon City - Arnold Sahalessy; Vando Kristi Makaruku (Peneliti.net, 2021)
Teacher performance does not just happen, but is influenced by certain factors. Both internal and external factors have an impact on teacher performance. Internal performance factors are factors that come from within a person that affect their performance such as: perception, field experience, motivation to become a teacher, family background, abilities, skills and personality. It needs to be realized that low teacher performance can reduce the quality of education and hinder the achievement of educational goals in schools. For this reason, teacher performance needs to be managed properly so that there is no decline. This study aims to determine the significant effect of learning leadership and work motivation on teacher performance. This study aims to determine the effect of learning leadership on teacher performance, the effect of work motivation on teacher performance and the effect of learning leadership and work motivation together on teacher performance. This research was conducted at State Junior High Schools in Baguala District, Ambon City. In this study using a quantitative descriptive method. The research method used is the correlation test method, partial and simultaneous using the SPSS 17.0 program. The results of this study indicate, 1) there is a significant influence of learning leadership on teacher performance with a value of tcount 2,222 and ttable 1,998, 2) there is a significant effect of work motivation on teacher performance with a value of tcount 4,441 and ttable 1,998, 3) there is significant influence of learning leadership and work motivation on teacher performance with a value of fcount 9.709 and ftable 3,150. The conclusion is that there is a significant influence of learning leadership and work motivation on teacher performance at State Junior High Schools in Baguala Kota District.